Effects of high energy electron and X-ray irradiation on the morphology, microstructure and reflectivity of cast speculum metal mirror. (January 2023) - Nazimudeen, E.A.; Girish, T.E.; Abraham, Sunila; Midhun, C.V.; Varier, K.M.
Abstract: The effects of irradiation of cast speculum metal mirrors using high-energy electrons (6 MeV and 9 MeV) and X-rays (6 MeV and 10 MeV) from a medical linear accelerator setup are studied in detail for the first time. Analyses using the techniques of X-ray diffraction, atomic force microscopy and Ultraviolet–Visible spectroscopy reveal that the irradiation causes some significant microstructural and morphological changes on the surface of speculum metal leading to the modifications of surface properties and hence the reflectivity of the material. From AFM morphology and XRD pattern, it is evident that the electron beam irradiation affects the surface topography and crystallographic properties of the material more at 6 MeV than 9 MeV. The optical studies suggest a significant reduction in Ultraviolet–Visible reflection after electron irradiation. However, X-ray irradiation of speculum metal provides an enhancement of reflection in the Ultraviolet–Visible region. Irradiation with high-energy electrons affects significantly the amount of absorption in the ultraviolet region. Moreover, an inverse relationship between crystallinity and visible reflectivity is inferred after electron and X-ray irradiations. These results may open up promising possibilities for this alloy to use in future space missions under high-energy irradiation due to its capacity to resist energetic particles and electromagnetic radiation without much material destruction. Graphical abstract: Irradiation of cast speculum metal mirror using high energy electrons and X-rays induce changes in the surface morphology, microstructure and topography of the material due to the creation of point defects and lattice deformations that may lead to the modifications of surface properties and hence reflectivity of the material. Cast speculum metal mirror shows enhanced reflection after high energy irradiation using X-rays and reduced reflection (enhanced absorption) after high energy electron irradiation. Image 1 Highlights: Investigated the irradiation effects on speculum metal using electrons and X-rays. Electron irradiation reduces reflection while X-ray irradiation enhances reflection. 6 MeV and 9 MeV electrons irradiation increase the absorption in the UV-C region. Irradiation changes the morphology, microstructure and hence optical reflectivity. Speculum metal finds application as an optical component in space and medical physics.